Post-voiding residual urine and capacity increase in orthotopic urinary diversion: Standard vs modified technique - Bančević Vladimir; Aleksić Predrag; Milović Novak; Košević Branko; Čampara Zoran; Stamenković Dušica (Vojnosanitetski Pregled)
Background/Aim. Ever since the time when the first orthotopic urinary diversion (pouch) was performed there has been a constant improvement and modification of surgical techniques. The aim has been to create a urinary reservoir similar to normal bladder, to decrease incidence of postoperative complications and provide an improved life quality. The aim of this study was to compare postvoiding residual urine (PVR) and capacity of the pouch constructed by standard or modified technique. Methods. In this prospective and partially retrospective clinical study we included 79 patients. In the group of 41 patients (group ST) pouch was constructed using 50-70 cm of the ileum (standard technique). In the group of 38 patients (group MT) pouch was constructed using 25-35 cm of the ileum (modified technique). Postoperatively, PVR and pouch capacity were measured using ultrasound in a 3-, 6- and 12-month period. Results. Postoperatively, an increase in PVR and pouch capacity was noticed in both groups. Twelve months postoperatively, PVR was significantly smaller in the group MT than in the group ST [23 (0-90) mL vs 109 (0-570) mL, p < 0,001]. In the same period the pouch capacity was significantly smaller in the MT group than in the ST group [460 (290-710) mL vs 892 (480-2 050) mL, p < 0.001]. Conclusion. Postoperatively, an increase in PVR and pouch capacity was noticed during a 12-month period. A year following the operation the pouch created from a shorter ileal segment reached capacity of the 'normal' bladder with small PVR. The pouch created by standard technique developed an unnecessary large PVR and capacity.